MENINGKATKAN PERHATIAN PESERTA DIDIK TERHADAP PEMBELAJARAN MELALUI BIMBINGAN KLASIKAL DENGAN MEDIA AUDIO VISUAL - Siti Rahmawati; Luhur Wicaksono; Purwanti Purwanti (Universitas Tanjungpura, 2019)
AbstrakStudents’ attention to learning activity is important because it can affect their learning achievement. Using audio-visual media is one solution and good strategy to increase their attention to the instruction because it can make the learning more varied and enjoyable. This study discusses increasing students' attention towards learning through classical guidance using audio-visual media in class X students of SMAN 4 Pontianak. Specifically, this research presents a discussion regarding how was students' attention to learning activity before using audio-visual media, how planning and implementing classical guidance was conducted, and how improvement was achieved after classical guidance using audiovisual media was implemented. 22 students participated as subjects in this study. The method used in this study was descriptive in the form of guidance and counseling action research. The research data was taken using observation and interviews. The findings showed an increase in student attention in learning by 78.2% with a high category after the selected media was applied. Keywords: Students' Attention, Audio-Visual Media, Classical Guidance